Reading in the experience biographies in Arabic and Malay poetry - Mohammed, Nafea hammad; Gawad, Siham Hasan (Opción, 2019)
The research aims to comparing the poetic biography in Arabicpoetry and Malay poetry to the importance of this literary genre.Research follows the method of analytical approach in the analysis ofself-dimensions and reading their approaches in the poetic text in aflexible coordinate tool. As a result, the Arab poet Ibrahim Nasrallahand the Malaysian poet Abdul Aziz Darman poets always resort to theretrieval of the past and experience. In conclusion, the spirit of writingin this framework reveals to us a social, intellectual and human mindenjoyed by the Arab and Malay personality.